Experimental Investigation, Application and Monitoring of a Simple for Dead Load--Continuous for Live Load Connection for Accelerated Modular Steel Bridge Construction - Javidi, Saeed; Yakel, Aaron; Azizinamini, Atorod (Engineering Journal, 2014)
The inherently modular nature of the simple for dead—continuous for live load system (SDCL) makes it a natural fit for the accelerated construction paradigm. A detail capable of connecting pre-topped girders over the middle supports is developed and described in this paper. To evaluate the performance of the proposed connection, a full-scale specimen was built and subjected to cyclic and ultimate load testing. The connection showed very little change during cyclic loading equivalent for 70 years of traffic. During the ultimate load test, the connection demonstrated large displacement ductility, reaching its ultimate capacity after complete yielding of the longitudinal reinforcement. After the successful experimental test, a field application bridge was constructed utilizing a modular pre-topped steel box girder system, which allows much of the construction process to be performed prior to placing the girders. The bridge consisted of three pre-topped steel box units placed side by side and connected using longitudinal joints between pre-topped units. The steel box girders used 70-ksi high-performance steel in the bottom flange and 50-ksi steel in the top flanges and webs. The use of high-performance steel combined with the simple for dead—continuous for live load system allows eliminating the need for section transitions through the length of the structure and using constant cross-section throughout the length of the girders. Long-term monitoring of the structure was performed and showed the system performed as intended.